Reducing Post-Harvest Loss in Developing Countries through the Feed the Future Initiative - Bhadra, Rumela (My University)
The Feed the Future Innovation Lab for the Reduction of Post-Harvest Loss (PHLIL), housed at Kansas State University (KSU), is a research and education program aimed at improving food security by reducing post-harvest loss of seeds and staple crops, such as grains, oilseeds, and legumes. Feed the Future is the U.S. Government’s initiative for food security and ending global hunger in developing countries. PHLIL’s efforts are focused in four Feed the Future countries—Bangladesh, Ethiopia, Ghana, and Guatemala—as well as Afghanistan as a short term engagement.
Citation: Bhadra, R. (2017). Reducing Post-Harvest Loss in Developing Countries through the Feed the Future Initiative. Resource Magazine. 24(3), 12-15.
Keywords: Feed the Future Innovation Labs; Post-Harvest Loss; Food Security; PHLIL